(untitled) (Bangladesh Medical Journal, 2024)
Laparoscopy has become the method of excellence for abdominal surgeries in modern age. The significance of a secure and dependable approach for the initial trocar insertion cannot be overstated in this surgical procedure. Our preferred method involves employing a modified open technique to access the peritoneal cavity. This study was conducted to evaluate the laparoscopic surgery of modified open technique. This cross sectional follow-up study was conducted in the Department of General Surgery Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2019 to December 2022. The umbilicus was everted to make it tubular, an infra-umbilical incision was given to cut the linea alba for making an opening and advanced bluntly to introduce the first port. A total of 197 patients were studied after completion of surgery. Cholecystectomy was the most common surgical indication. The mean entry time was 3.1±0.6 minutes. Regarding the postoperative complication port site infection was 2.03% and port site hernia was 1%. There was no incidence of pre-peritoneal placement of port, port site seroma, haematoma. No mortality was found during the hospital stay of patients. Modified open technique is a quick and safe procedure for insertion of the first port in laparoscopic surgery. Bangladesh Med J. 2023 May; 52(2): 11-14